Significance of Omega-3 fatty acids in the milk fat of dairy cows - Roy, Ashwani Kumar; Singh, Mahendra (Indian Farming, 2018)
Research has demonstrated that the abomasal infusion of SDAenhanced SBO resulted in a 5-fold increase in the n-3 fatty acid content of milk fat, specifically increasing ALA, SDA, ETA, and EPA. Relative to meeting the human dietary requirements for n-3 fatty acids, an increase in SDA has an advantage over ALA because humans can more efficiently convert SDA to EPA. However, results also indicate that rumen- protected formulations of SDA-enriched SBO would be needed to achieve increases in the n-3 fatty acid content of milk fat. Therefore, it clearly demonstrates the impressive potential to utilize SDA-enhanced soybeans to achieve increases in the n-3 fatty acid content of dairy products for larger benefits to human health.